Contextualizing sustainable competitive advantage: A perspective of social entrepreneurship - Prasetyo, Aries Heru (Journal of Entrepreneurship, Business and Economics, 2016)
This study aimed in contextualizing competitive advantage for social entrepreneurship from different perspective. Having defined social entrepreneurship as ways to have better solution in dealing with social issue, enterprise is believed to be founded upon some social mission. In that case, the role of commitment, loyalty and perseverance become an important concept to understand the characteristic of organization. One important signal found in the study was due to a rapid growth of development for the fields of knowledge. The study identified the important role of leadership and knowledge management to social enterprise. The three major contributions from the study are: (i) addressing the basic framework in analyzing social entrepreneurship, (ii) codifying possible network mapping faced by complex-social enterprise and (iii) proposing model for future competitive advantage by consider-ing unique characteristics of social organization. The study enclosed with proposing three proposi-tions which covered the relationship between social enterprise and the society and also some possibil-ity to have different analysis between developed and developing country. Research paper Reference to this paper should be made as follows: Prasetyo, A. H. (2017). “Contextualizing sustain-able competitive advantage: A perspective of social entrepreneurship”, Journal of Entrepreneurship, Business and Economics, Vol. 5, No. 1, pp. 41–66.